(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India is an agricultural country and one third population depends onthe agricultural sector directly or indirectly. Agriculture remains as the mainstray of the Indian economy since times immemorial. About 18 % of the country’sincome is from agriculture sector which provides employment to more than halfof the work force in the country. With food being the crowning need of mankind,much emphasis has been on commercializing agricultural production. In earlierdays when the village economy was more or less self-sufficient the marketing ofagricultural products presented no difficulty as the farmer sold his produce tothe consumer on a cash or barter basis. Since it would cause diversificationand commercialization of agriculture, it was thus enhance the incomes offarmers and create food surpluses. The agro-industry mainly comprises ofthe post-harvest activities of processing and preserving agricultural productsfor intermediate or final consumption. It is a well-recognized fact across theworld, particularly in the context of industrial development that theimportance of agro-industries is relative to agriculture increases as economiesdevelop.